ANALISIS KEPUASAN PELANGGAN TERHADAP BENIH PADI “PRIMA” DI KABUPATEN MALANG (JASEP, 2015)
The purpose of this study was to determine the level of satisfaction of farmers on " Prima " seed product based on the perception of Malang farmers. This research was conducted in Malang in February until March 2015. The data used in this study were primary data and secondary data. The number of respondents in this study as many as 50 farmers who have used seed products Ciherang " Prima " . The analysis method used in this research is Customer Satisfaction Index ( CSI ) . Based on this research, farmers satisfied with the performance of attributes in the seed products Ciherang " Prima " , this was indicated by the CSI value of 78.63 %.